Respectful Maternity Care: Concept Paper - Tsomondo, Ethel; Chihava, Itai; Kasu, Christine Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
There are varying perceptions regarding the meaning of respectful maternity care (RMC) among service providers and the women cared for despite being an area of concern for decades. Objective The objective of the concept paper was to determine what respectful maternity care means for the purpose of measuring it. Methodology Walker and Avant (2011) concept analysis model was used to guide this paper. The following search engines, Google Scholar, Pubmed and Medline were utilised to select 15 articles relevant to the concept of interest. Results: The meaning of RMC is not very clear to both clients and care givers, policies are not being translated to action fully for effective RMC Conclusion The curricula of care providers’ education to emphasise on affective domain skills and further research and action on findings to improve RMC.